Analysis of Growth Rings in Black Spruce (Picea mariana) in Relation to Site and Climatic Factors - Usik, Lily (My University, 1967)
The annual earlywood, latewood and total radial growth in black spruce from organic and mineral soils of varying depths, composition, ad moisture regimes of three locations in Ontario were investigated. Growth in relation to site, temperature, and precipitation was assessed. Statistical analyses of the radial width increments expressed as percentages of trend over thirty years' growth, showed significant crossdating. Total annual and earlywood increments are correlated with mean March-April and March temperature; latewood increments are not. There is no relationship between growth and precipitation. These findings hold for trees from organic and mineral soil sites up to approximately five hundred miles apart. It is concluded that spring mean temperature is independent of site or other climatic factors, and results suggest that spring temperature indirectly controls radial growth. Primary direct controls are presumably internal, i.e. physiologic and genetic.
Analysis of Growth Rings in Black Spruce
Keywords: tree rings; growth rings; black spruce; climatic factor